2013
DOI: 10.1073/pnas.1301799110
|View full text |Cite
|
Sign up to set email alerts
|

Aire-expressing thymic medullary epithelial cells originate from β5t-expressing progenitor cells

Abstract: The thymus provides multiple microenvironments that are essential for the development and repertoire selection of T lymphocytes. The thymic cortex induces the generation and positive selection of T lymphocytes, whereas the thymic medulla establishes self-tolerance among the positively selected T lymphocytes. Cortical thymic epithelial cells (cTECs) and medullary TECs (mTECs) constitute the major stromal cells that structurally form and functionally characterize the cortex and the medulla, respectively. cTECs a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

19
136
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 122 publications
(155 citation statements)
references
References 32 publications
19
136
0
Order By: Relevance
“…-2875 that CCRL1 + fetal cTECs contain mTEC progenitor activity. These results agree with the recent reports discussed above showing that pTECs progress through a stage in which they express cTECassociated molecules before diversifying into mTECs [11,[14][15][16] (Fig. 1).…”
supporting
confidence: 93%
See 4 more Smart Citations
“…-2875 that CCRL1 + fetal cTECs contain mTEC progenitor activity. These results agree with the recent reports discussed above showing that pTECs progress through a stage in which they express cTECassociated molecules before diversifying into mTECs [11,[14][15][16] (Fig. 1).…”
supporting
confidence: 93%
“…In those mice, EGFP expression would indicate current and/or past expression of β5t in the cells. It was found that β5t-Cremediated EGFP expression was detectable in almost all mTECs, including the Aire + subpopulation, throughout the ontogeny, indicating that a majority of mTECs, in which β5t expression is not detectable, are derived from β5t-expressing progenitors [16]. Collectively, the three independent reports [14][15][16] revealed a new stage in the TEC developmental pathways, i.e.…”
mentioning
confidence: 89%
See 3 more Smart Citations